THU0339 Impact of carotid ultrasound on the cardiovascular risk stratification of patients with systemic lupus erythematosus. (12th June 2018) - Quevedo Abeledo, J.C.; Sánchez, H.; Rua-Figueroa, I.; Tejera, B.; Naranjo, A.; Rodríguez-Lozano, C.; Ferraz-Amaro, I.
Abstract : Background: Autoimmune rheumatic diseases, including systemic lupus erythematosus (SLE), are associated with a significant increase in cardiovascular morbidity and mortality. The risk stratification instruments used in the general population underestimate the true risk of events in these patients. Carotid ultrasonography, through the detection of subclinical atheromatosis, is a powerful predictor of future cardiovascular events. The available evidence, endorsed in the official Prevention Guidelines, supports the use of this technique for the adequate identification of those patients of "very high risk", candidates for preventive interventions of greater intensity. Objectives: To analyse the cardiovascular risk profile, the prevalence of subclinical atheromatosis detected by carotid echography, and its implications in the prevention strategy in patients with SLE. Methods: A cross-sectional study of 276 patients diagnosed with SLE. The clinical characteristics and risk profile were analysed by SCORE. The presence of plaques and intima-media thickness (cIMT) was determined by carotid ultrasound and the cIMT percentiles were calculated according to tables adjusted for age and sex. Differences in risk stratification before and after carotid ultrasonography were determined by univariate regression analysis. The therapeutic implications after reclassification were evaluated according to the 2016 European Prevention Guides. Results: Risk stratification using SCORE was: low in 187 (67%), moderate in 73 (26%), and high or very high in 16 (6%). The median percentiles for cIMT were not statistically different from the p50 of healthy general population (p=0.54). Ultrasound showed the presence of plaque or cIMT >p75 or cIMT >0.90 mm in 60% (166) of the patients evaluated. The presence of this finding by risk categories was: low 102/187 (55%), moderate 55/73 (75%), high 7/9 (78%) and very high 6/7 (86%). According to the published guidelines, the detection of plaque carried out the re-stratification to a very high risk in 35% of patients. These patients where re-classification was achieved showed a higher SLICC index compared to those that did not change of category (mean difference 0.9 points, p=0.000). This difference remained statistically significant when the items related to cardiovascular risk that SLICC possesses were eliminated. SLEDAI and Katz were not statistically different between both groups. The SCORE of patients who were reclassified was also statistically higher (mean difference 0.7 points, p=0.021). Ninety percent of patients were re-classified to a very high risk had out-of-target LDL cholesterol levels for their new risk category (LDL <70 mg/dl). Similarly, only 46% of them were on statin therapy. Therefore, the indication or intensification of lipid-lowering treatment was followed only in 30% of the total evaluated. Conclusions: The reclassification of cardiovascular risk through the use of ultrasonography in SLE occurs in one third of patients. Our data suggests that this may be consequence of the damage produced by the disease. One in three candidates needed preventive interventions of greater intensity that had not been taken. Disclosure of Interest: None declared